Implementation Method Learning Role Playing for Improving Students' Understanding of Pancasila Values in Grade V of Derok Elementary School - Heriardus Riu Bere; Efrems Hendro Loe Loko; Rinawati Br Perangin Angin (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study aims to determine the application of the role playing learning method in improving students' understanding of Pancasila values ​​in grade V of SDI Derok, Raihat District, Belu Regency, East Nusa Tenggara. The background of this study is the low level of students' understanding of the meaning of the Pancasila principles, which is seen from their lack of discipline, low cooperation, and minimal sense of responsibility in school activities. This study uses a descriptive qualitative approach with the type of Classroom Action Research (CAR) which is carried out in two cycles. Each cycle includes four stages, namely: planning, implementation, observation, and reflection. The research subjects consisted of 20 grade V students of SDI Derok. Data were collected through observation, interviews, comprehension tests, and documentation. Data analysis was carried out descriptively qualitatively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of the role playing method can improve students' understanding of Pancasila values. In the initial condition, only 46% of students understood the meaning of the Pancasila principles well. After implementing the role-playing method in cycle I, understanding increased to 54.54%, and in cycle II, it increased again to 86.36%. In addition to cognitive improvements, positive attitude changes occur, such as student cooperation, responsibility, and discipline during learning activities. Thus, the role-playing learning method has proven effective in improving the understanding and practice of Pancasila values ​​in elementary schools. This method also makes learning more meaningful, interactive, and enjoyable for students.